Optimal convergence rates for the strong solutions to the compressible Navier–Stokes equations with potential force. (April 2017) - Wang, Wenjun
Abstract: In this paper, we consider the effect of external force on the large-time behavior of solutions to the Cauchy problem for the three-dimensional full compressible Navier–Stokes equations. We construct the global unique solution near the stationary profile to the system for the small H 2 ( R 3 ) initial data. Moreover, the optimal L p – L 2 ( 1 ≤ p ≤ 2 ) time decay rates of the solution to the system are established via a low frequency and high frequency decomposition.